Cladistic analysis and description of three new species of the Chilean genus Nanophareus (Opiliones: Gonyleptidae: Pachylinae) - Hara, Marcos Ryotaro (Zootaxa, 2016)
Three new species of the Chilean Pachylinae genus, Nanophareus Roewer, 1929 are described: N. bicornutus sp. nov. (Valle de Aconcagua, Zapallar, V Región de Valparaíso), N. maipu sp. nov. (La Rinconada, Quebrada de la Plata, Maipu, Región Metropolitana—Santiago), and N. polyhastatus sp. nov. (El Abanico, VIII Región de Bio-Bío). These three new species were included in a cladistic analysis that resulted in two equally most parsimonious trees (238 steps, C.I. = 0.38; R.I. = 0.51), corroborating the monophyly of Nanophareus. The proposed synapomorphies for Nanophareus remain largely unchanged: an external row of enlarged tubercles inserted amongst small ones on the lateral margin of dorsal scutum; the ventro-basal margin of the pedipalpal tibia curved at 90° in lateral view; and retrolateral seta on pedipalpal tibia with an apically bifid socket (socket and seta longer than pedipalpal tibia length), with additional small setae distally. The sister group of Nanophareus, as well as its subfamilial placement, are still unsettled issues that are here further discussed.